Cost-effectiveness of esomeprazole and pantoprazole as prophylaxis stress-related mucosal disease therapy in Intensive Care Unit - Ferina Damayanti; Endang Darmawan; Setiawan Didik (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2021)
High risk of bleeding in a patient with a critical condition in an Intensive Care Unit (ICU) resulting requirement use needs prophylaxis for decrease bleeding incident during ICU is entirely accurate. This research is to determine the cost and effectiveness of esomeprazole and pantoprazole as Stress Related Mucosal Disease (SRMD) in the hospital ICU in Surakarta. This research is a retrospective cohort study. The subject is about all inpatients in ICU with the age of 18 to 65 who get esomeprazole and pantoprazole as stress ulcers prophylaxis during December 2016 – December 2018 that meets the criteria inclusion and exclusion criteria. Subjects on this research are 166 patients, where each group esomeprazole therapy (83 patients) and pantoprazole (83 patients). The effectiveness of treatment was observed based on the minor and major bleeding. Furthermore, the cost of therapy is calculated based on the total price paid by the patient for prophylaxis therapy on SRMD and treatment bleeding SRMD that count as Incremental cost-effectiveness ratio (ICER) value. The research result shows that no real difference between patients treated with esomeprazole (88%) and pantoprazole (80,7%) as prophylaxis therapy SRMD (p = 0.286). The use of esomeprazole can save money by IDR 13,456,368.00 (ICER) compared to pantoprazole for each cost reduction in the event of bleeding.